The Role of Individual Performance in the Effect of ICT Appropriation on Educational Performance of Students in Public Universities in the Casablanca-Settat Region, Morocco - Mdarbi, Said; Simour, Lhoussain; Boufarouj, Chaimae; Belkebir, Zineb; Stili, Khadija; Ennadi, Mouad (European Scientific Journal, ESJ, 2024)
Over the past two decades, Moroccan higher education institutions have significantly invested in information and communication technologies (ICT). The integration of ICT in education (ICTE) and learning has led to major changes, including the implementation of digital strategies and programs that have enriched the educational system. Notable progress has been made, such as providing most institutions with computer equipment and expanded internet access, especially in universities. Despite these advancements, questions remain about the true impact of these technologies on student performance and the overall effectiveness of the educational system. While researchers have explored this issue both theoretically and empirically, they face challenges, including the complex observation of students’ individual performance and the rapid evolution of ICT, which makes isolating their effects difficult. This study aims to examine the impact of students’ appropriation of ICT on educational performance in public universities in the Casablanca-Settat region and to explore the role of individual performance in this relationship. Using structural equation modeling (SEM) with SMART PLS 4.0 software, data from 185 students revealed a significant positive relationship between ICT appropriation and educational performance, with individual performance serving as a mediator. By employing mediation analysis, as outlined by Baron and Kenny (1986) and MacKinnon et al. (2007, 2012), the study investigated how individual performance mediates the relationship between ICT appropriation and educational performance. This method enabled the identification of both direct and indirect effects, providing a more nuanced understanding of the mechanisms through which ICT impacts educational outcomes via individual performance. The findings suggest that ICT is a crucial factor in improving higher education performance and highlight the importance of platform quality and students’ sense of self-determination in the effective integration of ICT in the educational process. Future research should continue to explore individual performance among Moroccan university students and its impact on educational outcomes.